Análise do Ácido Glicólico como solução para remoção da Smear Layer de canais radiculares - Barcellos, Débora Pereira Diniz Correia (2018)
Considering that during the endodontic treatment the smear layer should be removed and the EDTA has some unfavorable characteristics, the objective of this study was to evaluate the smear layer removal capacity and the effects of Glycolic Acid (GF) on the radicular dentin surface. Twenty unirradicular teeth were sectioned longitudinally in the middle and the forty segments were randomly divided into four groups as follows: negative control, saline; EDTA 17%; AG 17% with pH 1.2; and AG 17% at pH 5. Two ml of 2.5% NaOCl was initially applied to all samples for 1 minute, followed by 5 ml of saline irrigation, shortl y after 2 ml of the solution tested acted for 1 minute and finally 5 ml of saline irrigation in order to evaluate the dentin microhardness. Another forty unirradicular human teeth were submitted to rotational instrumentation with sodium hypochlorite (NaOCl) and soon after randomly divided into 4 groups in the same way as the previous test. The roots were cleaved longitudinally and analyzed by scanning electron microscopy (SEM) to determine the presence or absence of smear layer, root dentin erosion and mineral content distribution. Data were tabulated and submitted to statistical analysis. The highest microhardness value was obtained by the control group irrigated with saline solution. The groups that received EDTA and AG at both pHs had microhardness values lower than the